2022
DOI: 10.3390/cells11131990
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Complex: A Signaling Hub in Cancer

Abstract: The Golgi Complex is the central hub in the endomembrane system and serves not only as a biosynthetic and processing center but also as a trafficking and sorting station for glycoproteins and lipids. In addition, it is an active signaling hub involved in the regulation of multiple cellular processes, including cell polarity, motility, growth, autophagy, apoptosis, inflammation, DNA repair and stress responses. As such, the dysregulation of the Golgi Complex-centered signaling cascades contributes to the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 163 publications
0
18
0
Order By: Relevance
“…Interestingly, the Golgi apparatus and mitochondria have been found to be in close contact through imaging techniques [36] yet the molecular details are unclear. The GC as a central hub coordinates multiple cellular processes, motility, growth, autophagy, apoptosis, inflammation, stress responses, and DNA repair [37]. GC-centered signaling cascades do indeed contribute to cancer.…”
Section: Golgi Complex: Ground Zero For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Golgi apparatus and mitochondria have been found to be in close contact through imaging techniques [36] yet the molecular details are unclear. The GC as a central hub coordinates multiple cellular processes, motility, growth, autophagy, apoptosis, inflammation, stress responses, and DNA repair [37]. GC-centered signaling cascades do indeed contribute to cancer.…”
Section: Golgi Complex: Ground Zero For Cancermentioning
confidence: 99%
“…GC-centered signaling cascades do indeed contribute to cancer. There are targets on the trans-Golgi and cis-Golgi sides [37]; starting with the trans-Golgi there are targets such as EGFR, mTORC1 that converge on SCAMP3. Wnt/B-catenin, NFκB, IRF, TLR, ERK-MAPK, JNK-MAPK converge on Sef.…”
Section: Golgi Complex: Ground Zero For Cancermentioning
confidence: 99%
“…The GA as a central hub coordinates multiple cellular processes, motility, growth, autophagy, apoptosis, inflammation, stress responses, and DNA repair [40]. GA-centered signaling cascades do indeed contribute to cancer.…”
Section: Golgi Apparatus: Ground Zero For Cancermentioning
confidence: 99%
“…GA-centered signaling cascades do indeed contribute to cancer. There are targets on the trans-Golgi and cis-Golgi sides [40]; starting with the trans-Golgi there are targets such as EGFR, mTORC1 that converge on SCAMP3. Wnt/B-catenin, NFκB, IRF, TLR, ERK-MAPK, JNK-MAPK converge on Sef.…”
Section: Golgi Apparatus: Ground Zero For Cancermentioning
confidence: 99%
“…In addition to these canonical functions, the Golgi apparatus is now recognized as a signaling hub for mediating various cellular processes such as cell growth, mitosis, apoptosis, autophagy, ferroptosis and stress responses [ 4 , 5 , 6 , 7 ]. It has been demonstrated that altered signaling events within the Golgi apparatus contribute to the development of various diseases, including cancer [ 8 , 9 , 10 , 11 ]. These cancer-adapted signaling processes can be viewed as a vulnerability of cancer cells that can be exploited for development of selective anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%